Evaluation of an informational and behavior change program to increase students' self‐reported energy conservation. (24th May 2017) - Desrochers, Marcie N.; Mosher, Hilary
Abstract : A systematic evaluation of a program, consisting of sustainability education, self‐management strategies, and feedback, to decrease college students' energy use was conducted. During treatment, the experimental group showed increased self‐reported energy savings relative to baseline levels and relative to the self‐reported energy use of the comparison group who were shown only an instructional video on conserving energy. Treatment gains were maintained at a 2‐week follow‐up. More participants in the experimental group rated their experience as resulting in learning something new about green issues and influencing their pro‐environmental behavior compared to the comparison group. This study suggests that further research is warranted, specifically using these strategies in real‐life situations.